Basic Parameters of 6-10 kV Transmission Lines Reliability - G. F. Kutsenko; O. Yu. Pukhalskaya (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2006)
Operational parameters of 6-10 kV transmission lines reliability such as number of emergency interruptions, interruption frequency, average duration of interruption are investigated. Histograms of interruption distribution in numbers, average duration of interruption in 6-10 kV networks in months of a year, number of interruptions in hours of a day are constructed. The analysis of the reasons of failures in power supply in 6-10 kV networks is executed.